Mesoporous titania/tungstophosphoric acid composites: suitable synthesis of flavones - Pérez, María Emilia (2013)
Mesoporous TiO₂/H₃PW₁₂O₄₀ composites were synthesized by sol–gel reactions using urea as a low-cost template, and adding tungstophosphoric acid (TPA) at the same time as the template. The TPA concentration was varied in order to obtain TPA contents of 0, 10, and 20 (w/w) in the solid. The samples presented mesopores with a diameter higher than 3.0 nm. The specific surface area of the solids decreased with both the increase of the TPA content and the calcination temperature. From Fourier transform infrared and ³¹P magic angle spinning-nuclear magnetic resonance studies it was observed that the main heteropolyoxometallate species present in the composites is the [PW₁₂O₄₀]³⁻ anion, which was partially transformed into the [P₂W₂₁O₇₁]⁶⁻ and [PW₁₁O₃₉]⁷⁻ anions during the synthesis and drying step. The X-ray diffraction patterns of the modified samples only exhibited the characteristic peaks of the anatase phase of titanium oxide. The point of zero charge decreased with both the increase of TPA content in the solids and the calcination temperature. The materials were found to be efficient and recyclable catalysts for the synthesis of a series of flavones. The reaction was carried out in different reaction media: heterogeneous and solvent-free conditions. The solvent-free conditions represent the best green conditions. Initially, we optimize the reaction condition to obtain 6-chloroflavone by direct reaction of the cyclodehydration of 1-(2-hydroxy-5-chlorophenyl)-3-phenyl-1,3-propanodione in the presence of a catalytic amount of mesoporous titania modified with tungstophosphoric acid catalyst. Reactions were performed in two conditions: low volume of toluene, at 110 °C, typically 24 h, and solvent-free at the same temperature, 1 h. In all cases the product (6-chloroflavone) was obtained with high selectivity. Conversions up to 76 and 92 % were obtained respectively, using the supported catalyst (TiTPA10). Optimal reaction conditions were applied to the preparation of six substituted flavones in both conditions.